2019
DOI: 10.1155/2019/5398732
|View full text |Cite
|
Sign up to set email alerts
|

Antierythropoietin Antibody Production Is Not Associated with Malaria and Malaria-Related Anaemia in Humans

Abstract: Introduction. The pathophysiology of malaria-related anaemia is not fully understood although increased destruction of parasitized and nonparasitized erythrocytes, as well as inadequate erythropoiesis, has been proposed. Circulating antierythropoietin (anti-EPO) antibodies have also been implicated in malaria and malaria-related anaemia in mice. However, studies on this association have not been investigated in humans. This study therefore determined the prevalence of anti-EPO antibody production and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
8
2
1
Order By: Relevance
“…Regression analysis from our study, revealed that malaria increases the risk of anemia by two-folds among the population. Other studies have also reported increased risk of anemia with malaria among pregnant women in Ghana and elsewhere [ 35 , 37 , 53 55 ] This finding could be linked to the intricate relationship between malaria and anemia such as malaria-induced destruction of non-parasitized and parasitized red cells, impaired erythropoiesis and delayed reticulocyte response due to suppression of the normal erythropoietin response during periods of tissue hypoxia [ 14 – 16 ]. Nonetheless, it is worthy of note that, malaria contributed only 4.5%, 0.3% and 0.3% to the prevalence of mild, moderate and severe anemia, respectively, suggesting that the presence of other factors, as indicated in this study, also play important roles in anemia in pregnancy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regression analysis from our study, revealed that malaria increases the risk of anemia by two-folds among the population. Other studies have also reported increased risk of anemia with malaria among pregnant women in Ghana and elsewhere [ 35 , 37 , 53 55 ] This finding could be linked to the intricate relationship between malaria and anemia such as malaria-induced destruction of non-parasitized and parasitized red cells, impaired erythropoiesis and delayed reticulocyte response due to suppression of the normal erythropoietin response during periods of tissue hypoxia [ 14 – 16 ]. Nonetheless, it is worthy of note that, malaria contributed only 4.5%, 0.3% and 0.3% to the prevalence of mild, moderate and severe anemia, respectively, suggesting that the presence of other factors, as indicated in this study, also play important roles in anemia in pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…Other factors such as socio-demographic and economic factors such as place of residence and educational level also play important roles [ 13 ]. The relationship between malaria and anemia is in the role played by malaria in the depletion of non-parasitized erythrocytes, immune destruction of parasitized red cells, and impaired erythropoiesis as a result of bone marrow dysfunction [ 14 – 16 ]. Malaria accounts for an estimated 3–15% of anemia and 25% of severe anemia in pregnant women from malaria-endemic countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is a pervasive parasitic disease in the tropical and subtropical regions which is mostly prevalent in sub-Saharan Africa, Asia, and Latin America [1]. Currently, the World Health Organization (WHO) estimates 219 million cases and 435,000 malaria-related deaths globally [2].…”
Section: Introductionmentioning
confidence: 99%
“…En líneas generales, las infecciones palúdicas producen del 3 % al 15 % de los casos de anemia, la cual resulta de la depleción de eritrocitos no parasitados con liberación de merozoitos, destrucción inmunológica de eritrocitos parasitados, pérdida de la deformabilidad del glóbulo rojo, y/o de la disfunción de la médula ósea que genera un proceso de eritropoyesis inefectiva. Pero, de estos, el 25 % de los mismos constituyen casos de anemia grave en las embarazadas que habitan en regiones endémicas, producto del secuestro eritrocitario placentario, hemólisis, eritropoyesis inefectiva, inhibición de la liberación de reticulocitos, destrucción prematura de los eritrocitos durante su fase de maduración en la médula ósea, e/o hiperesplenismo (2,14,35,(52)(53)(54)(55)(56). La anemia grave se define como valores de hemoglobina menores a 7 g/dl y esta puede ocasionarle a la gestante con infección malárica una alta morbimortalidad maternofetal y complicaciones como fetos de bajo peso al nacer, parto pretérmino y muerte por hemorragia posparto.…”
Section: Manifestaciones Clínicas Y Complicaciones Maternofetalesunclassified